2020
DOI: 10.7150/thno.43473
|View full text |Cite
|
Sign up to set email alerts
|

Flubendazole elicits anti-cancer effects via targeting EVA1A-modulated autophagy and apoptosis in Triple-negative Breast Cancer

Abstract: Background: Triple-negative breast cancer (TNBC) is one of the most prevalent neoplastic diseases worldwide, but efficacious treatments for this pathological condition are still challenging. The lack of an effective targeted therapy also leads to a poor prognosis for patients affected by TNBC. In the present study, we repurposed the distinctive inhibitory effects of flubendazole, a traditional anthelmintic drug, towards the putative modulation of proliferation and migration of TNBC in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 60 publications
3
60
0
Order By: Relevance
“…Several studies have shown that autophagy may occur upstream of apoptosis 29 , 30 . To determine whether PNO1-mediated autophagy is related to apoptosis in HCC cells, we used rapamycin and 3-MA to activate and inhibit autophagy, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that autophagy may occur upstream of apoptosis 29 , 30 . To determine whether PNO1-mediated autophagy is related to apoptosis in HCC cells, we used rapamycin and 3-MA to activate and inhibit autophagy, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between autophagy and apoptosis is known to be complex. Accumulating evidence shows that autophagy and apoptosis usually occur within the same cell, and autophagy may serve as upstream regulation mechanism of apoptosis 29 , 30 , 54 . According to the different interactions of autophagy and apoptosis in tumor, it could be divided into synergistic, promoting, and antagonistic effects 37 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the EVA1 family includes three main groups: EVA1A, EVA1B, and EVA1C. Previous studies have revealed that EVA1A, an endoplasmic reticulum-related protein were involved in regulating autophagy and apoptosis-related mechanisms in many cancers (11,12). Additionally, Bang-Yi Lin et al found that EVA1A promotes papillary thyroid cancer progression and epithelial-mesenchymal transition via upregulating immunerelated signaling pathways (11).…”
Section: Introductionmentioning
confidence: 99%
“…Flubendazole, a broad-spectrum anthelmintic drug belonging to benzimidazole group, has been repurposed as a promising anti-cancer agent 94 . Zhen et al revealed flubendazole induced autophagic cell death by targeting Eva-1 homolog A (EVA1A) and suppressed TNBC proliferation and migration 95 . Moreover, resistomycin, QN-1 and emodin attenuates TNBC progression via binding to Pellino-1 to promote FBXO11-mediated SNAIL/SLUG degradation 96 , down-regulating c-MYC transcription 97 and reducing VEGFA transcription 98 , respectively.…”
Section: Novel Therapeutic Targets and New Drugsmentioning
confidence: 99%